A filosofia no ensino médio nos documentos pós LDB 9.394/96: avanços e desafios na organização curricular - Kapczynski, Ana Lucia (2016)
This study‟s central theme is situated in the curricular organization of Philosophy in High School in the post-LDB 9.394 / 96 period, in two moments: a) interdisciplinary orientation by the National Curricular Guidelines for Secondary Education of 1998; B) compulsory disciplinary teaching as stated in Law 11684/08. The study was motivated by the concerns arisen along the supervised internship during the undergraduate course in Philosophy (UPF / 2012) and by the interventions of PIBID in 2013. Given that the philosophical experiences in High School are embryonic due to discontinuities in previous periods, the present dissertation reclaims the references assigned to the curricular organization starting with the Law of Guidelines and Bases (LBD) 9.394 / 96, with the purpose of analyzing the advances of the actions taken in defense of Philosophy which resulted in achievements in LDB and Law 11.684 / 08 and the challenges that are still present in the structuring of the quality teaching of Philosophy. The hermeneutic interpretative approach of the literature produced on the subject, associated to the documentary analysis, ground the reflections and constitute the carried out research. As a result of the research, it can be observed that having Philosophy back in the curriculum has brought certain advances such as the contribution of specific knowledge to the intellectual and citizen formation of students, the revitalization of undergraduate courses and the creation of work spaces for graduates in Philosophy . However, there is no touchable presence of Philosophy as a school discipline, a philosophical culture consolidated in Basic Education, making the policies for teaching Philosophy to become generic, partial and insufficient to assert a national program. The emphasis on making Philosophy and the weakening of the studies on classical texts, in fear of indoctrination, can sometimes institute a barrier for the access to scholarly philosophy, challenging a better definition of what disciplinary teaching really is, a task still unfinished within the scope of curricular organization in high school and the demands for teacher training.